Educação matemática e crianças surdas: explorando possibilidades em um cenário para investigação - Moura, Amanda Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation describes a study that aimed to establish an understanding of the engagement of deaf children in proposed landscapes of investigation. For this, were made landscapes of investigation using simulation softwares related Activities Practice Life. We sought to investigate whether the environment in which the investigation was carried out makes room for discussions about mathematics and how mathematics can contribute to the autonomy and social inclusion of people with disabilities, focusing on deaf people. The group of participants consisted of deaf children attending a rehabilitation institution that provides care to people with disabilities, having as one of the main goals the social inclusion. These children were aged between seven and nine and they had different command of Brazilian sign language. The work strategy followed the molds qualitative research in mathematics education, with recorded observations in a diary, filming and interview. The analysis was conducted from three concepts considered fundamental in the proposal of the landscapes of investigation. These concepts are related with the good reasons of the participants to accept or not the invitation to research, the dialogic acts that constitute the Investigative Cooperation Model and the risks and obstacles present in the process. Such concepts were listed by the researcher and, based on them, were discussed the factors that stood out in the engagement of children with the research proposal. The problems arising from late exposure to sign language by participants, reflected in the investigative action. The factors influencing the engagement of children with activities showed up complex and very private. However, the results of this research showed the landscapes of investigation as an enabling environment and as a new methodological possibility for teaching and learning of mathematics to deaf people. In addition, raises new questions for future research

Esta dissertação descreve uma pesquisa que teve como objetivo estabelecer uma compreensão sobre o engajamento de crianças surdas em uma proposta de cenários para investigação. Para isso, foram constituídos cenários de investigação utilizando-se de softwares de simulação relacionados a Atividades de Vida Prática. Buscou-se investigar se o ambiente no qual foi realizada a investigação possibilita discussões matemáticas, bem como de que forma a matemática pode contribuir para a autonomia e inclusão social de pessoas com deficiência, com enfoque nas pessoas surdas. O grupo de participantes foi constituído por crianças surdas que frequentavam uma Instituição de Reabilitação que oferece atendimento a pessoas com deficiência, tendo como um dos principais objetivos sua integração social. Essas crianças estavam com idades entre sete e nove anos e apresentavam diferentes domínios da língua brasileira de sinais. A estratégia de trabalho seguiu os moldes de uma pesquisa qualitativa em Educação Matemática, com observações registradas em caderno de campo, filmagens e entrevista. A análise foi conduzida a partir de três conceitos considerados fundamentais na proposta de cenário para investigação. Tais conceitos estão relacionados ao aceite ou não dos participantes para o convite para investigação, aos atos dialógicos que constituem o Modelo de Cooperação Investigativa e aos riscos e obstáculos presentes no processo. Tais conceitos foram elencados pela pesquisadora e, com base neles, discutiram-se os fatores que se destacaram no engajamento das crianças com a proposta de investigação. As dificuldades decorrentes da exposição tardia a língua de sinais por parte dos participantes, refletiram-se na ação investigativa. Os fatores que influenciam no engajamento das crianças com as atividades se mostraram complexos e muito particulares. Contudo, os resultados desta pesquisa, mostraram os cenários para...
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Surdos - Educação; Deficientes auditivos; Crianças surdas; Educação especial; Educação inclusiva; Software